2016
DOI: 10.1007/s41061-016-0063-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Grafting for the Functionalization and Development of Smart Polymeric Materials

Abstract: Gamma radiation has been shown particularly useful for the functionalization of surfaces with stimuli-responsive polymers. This method involves the formation of active sites (free radicals) onto the polymeric backbone as a result of the high-energy radiation exposition over the polymeric material. Thus, a microenvironment suitable for the reaction among monomer and/or polymer and the active sites is formed and then leading to propagation to form side-chain grafts. The modification of polymers using high-energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 129 publications
0
25
0
Order By: Relevance
“…19,22 The acid groups become ionized and swell when they are in basic pH medium. 19,22 The acid groups become ionized and swell when they are in basic pH medium.…”
Section: Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…19,22 The acid groups become ionized and swell when they are in basic pH medium. 19,22 The acid groups become ionized and swell when they are in basic pH medium.…”
Section: Characterizationmentioning
confidence: 99%
“…On the other hand, PAAc is a pH-responsive polymer, which change its swelling behavior by changes in pH medium. 19,22 The acid groups become ionized and swell when they are in basic pH medium. Thus, grafting of PAAc was expected to communicate pH-responsiveness to the PEBA copolymer.…”
Section: Article Wileyonlinelibrarycom/appmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, radiation‐grafted low‐density polyethylene (LDPE) poly(vinylbenzylchloride)‐based AEMs reported by Wang et al demonstrated a peak power density of 1.45 W cm −2 at 80 °C. However, the radiation grafting of LDPE could lead to possible degradation of the polymer matrix, severely impacting the mechanical strength of the membrane . Additionally no long‐term device performance data were reported for these AEMs …”
Section: Introductionmentioning
confidence: 99%